HUBUNGAN DUKUNGAN KELUARGA DENGAN KUALITAS HIDUP PASIEN HIV/AIDS DI POLIKLINIK VCT RSUP SANGLAH DENPASAR - Kusuma Antari (Coping: Community of Publishing in Nursing, 2014)
HIV/AIDS was an infectious disease with no cure. The disease also had a "window period" and the asymptomatic phase  (without symptoms) was  relatively  long in the disease process.  People  infected  with  HIV/AIDS  experienced  physical  problems,  psychological, increased dependency, social relationships, environment and spirituality.   The complexity of these  issues  resulted  in  a  decreased  quality  of  life  of  patients  wit h  HIV/AIDS.  This  study aimed to analyze the relationship between family support  and  quality of life of patients with HIV/AIDS in VCT Department of RSUP Sanglah Denpasar . This research was observational analysis  with  cross  sectional  approach  used  consecutive  sampling  technique,  and  sample obtained by  120  respondents.  This research was conducted on May 4th–  June 4th2013. This research  used  guidance  of  Family  Support  and  WHOQOL-HIV  BREF  (World  Health Organization  Quality  of  Life-HIV  BREF)  questionnaires.  The  study  found  that  most respondents  (74,2%)  had  a  high   family  support  and  data  about  the  quality  of  life  for  the majority of respondents obtained results (70,8%) had a good quality of life.  Results of  ChiSquare statistical test at a significance level of ? = 0,05 obtained results p = 0, 000 (p < ?) and OR = 18,448,  means that there was  a relationship between family support  and  quality of life of  patients  with  HIV/AIDS  in  VCT  Department  of  RSUP  Sanglah  Denpasar .  Respondents who received family support 18 times higher chance to had a poor quality of life compared to respondents with high family support.